Isotopic order, biogeochemical processes, and earth history - Goldschmidt Lecture, Davos, Switzerland, August 2002 - Hayes, J. M. (Geochimica Et Cosmochimica Acta, 2004)
The impetus to interpret carbon isotopic signals comes from an understanding of isotopic fractionations imposed by living organisms. That understanding rests in turn on studies of enzymatic isotope effects, on fruitful concepts of isotopic order, and on studies of the distribution of (13)C both between and within biosynthetic products. In sum, these studies have shown that the isotopic compositions of biological products are governed by reaction kinetics and by pathways of carbon flow.Isotopic compositions of individual compounds can indicate specific processes or environments. Examples include biomarkers which record the isotopic compositions of primary products in aquatic communities, which indicate that certain bacteria have used methane as a carbon source, and which show that some portions of marine photic zones have been anaerobic. In such studies, the combination of structural and isotopic lines of evidence reveals relationships between compounds and leads to process-related thinking. These are large steps. Reconstruction of the sources and histories of molecular fossils redeems much of the early promise of organic geochemistry by resolving and clarifying paleoenviron-mental signals. In turn, contemplation of this new information is driving geochemists to study microbial ecology and evolution, oceanography, and sedimentology. Copyright (C) 2004 Elsevier Ltd.
813fdTimes Cited:17Cited References Count:70